Language across difference ethnicity, communication, and youth identities in changing urban schools - Paris, Django (Cambridge University Press, 2011)
"Once a predominantly African American city, South Vista opened the twenty-first century with a large Latino/a majority and a significant population of Pacific Islanders. Using an innovative blend of critical ethnography and social language methodologies, Paris offers the voices and experiences of South Vista youth as a window into how today's young people challenge and reinforce ethnic and linguistic difference in demographically changing urban schools and communities. The ways African American language, Spanish and Samoan are used within and across ethnicity in social and academic interactions, text messages and youth authored rap lyrics show urban young people enacting both new and old visions of pluralist cultural spaces. Paris illustrates how understanding youth communication, ethnicity and identities in changing urban landscapes like South Vista offers crucial avenues for researchers and educators to push for more equitable schools and a more equitable society"--